Direct Reaction of Amides with Nitric Oxide To Form Diazeniumdiolates - Holland, Ryan J. (American Chemical Society, 2014)
[Image: see text] We report the apparently unprecedented direct reaction of nitric oxide (NO) with amides to generate ions of structure R(C=O)NH–N(O)=NO(–), with examples including R = Me (1a) or 3-pyridyl (1b). The sodium salts of both released NO in pH 7.4 buffer, with 37 °C half-lives of 1–3 min. As NO-releasing drug candidates, diazeniumdiolated amides would have the advantage of generating only 1 equiv of base on hydrolyzing exhaustively to NO, in contrast to their amine counterparts, which generate 2 equiv of base.